KONSEPSI GURU TENTANG BELAJAR DAN MENGAJAR DALAM PERSPEKTIF BELAJAR AKTIF - - Pardjono (Faculty of Psychology, Universitas Gadjah Mada, 2000)
This case study was carried out in 1998 by employing a qualitativinterpretive tradition to invstigate teacher’s conception of the nature of learning and teaching from the Active Learning point of view. The eight school were selected from kecamaan Sewon, Bantul and Kecamatan Umbulharjo Yogyakarta based on the Sub-district educaional Authority. Teachers selected to participate in this study were the best teachers in term of their impleentation of Active Learning in the classroom from each of those schools as recommended by the Principal. Data were gathered by interviewing teachers sample. The data gathered was transcribed then sent to the interviewee for validation, then coded and analyzed. The grounded theory principles of coding were used in analyzing data. This study identified three types of teacher’s conception of learning and teaching from Active Learning approach perspectives: the traditional views, process skill views and constructivist view. It is suggested for further research aimed at investigating to what extent are the teachers able to implement their beliefs and conception of the nature of learning ang teaching into classroom practice. Keywords: theory of learning-active, learning-educational philosophy